COMPARATIVE ANALYSIS OF WATER COLUMN TEMPERATURE USING SEISMIC INVERSION AND WORLD OCEAN ATLAS (WOA) METHODS IN WAIPOGA WATERS, PAPUA - Kusdiana, Dias; Manik, Henry Munandar; Nainggolan, Tumpal Bernhard; Firdaus, Yulinar (Jurnal Perikanan Unram, 2025)
Seismic oceanography is a combination of two sciences: seismic and oceanography. It is used to study phenomena in the water column, one of which is temperature measurement in the water column. This study aims to analyze the differences in water column temperature measurements using the seismic inversion method and measurements using data from the World Ocean Atlas (WOA). The data processing is divided into three stages: seismic data processing using ProMAX 2D software, synthetic seismogram processing using Hampson-Russell Software, and temperature distribution processing using Ocean Data View and Matlab software. The accuracy of the inversion-derived temperature was tested against observational data using the mean absolute error (MAE) criterion. The results of the temperature difference analysis show that the temperatures obtained from WOA data measurements are lower than those obtained using the seismic inversion method. The temperatures measured using WOA data range from 27.5–29.4 °C, while the inversion method ranges from 30.8–29.3 °C. Verification results indicate fairly good accuracy, with the MAE between WOA and seismic inversion ranging from 1.9–3.4 °C.